The impact of early orthodontic intervention on dental and skeletal development in children with mixed dentition - Avreet Sandhu; Brinda A Sakaria; Sejal D Patel; Gaurav Ahuja; Neeldipsinh Jadeja; Aaryan Mehta; Dinta Kakkad (Wolters Kluwer Medknow Publications, 2024)
Background: The mixed dentition stage in children is a critical period for orthodontic assessment and intervention. This study investigates the effects of interceptive orthodontics on dental and skeletal development in children with mixed dentition, aiming to evaluate the potential benefits of early orthodontic treatment. Materials and Methods: A retrospective analysis was conducted on a cohort of 150 children with mixed dentition (aged 7-11 years), who received interceptive orthodontic treatment. Dental and skeletal records, including cephalometric radiographs and dental cast models, were collected before and after treatment. A control group of 150 untreated children with mixed dentition was also assessed for comparison. Various dental and skeletal parameters, such as dental alignment, overjet (OJ), overbite (OB), and cephalometric measurements, were recorded and analyzed. Results: The results of this study indicate significant improvements in dental alignment and occlusion in the group of children who received interceptive orthodontic treatment. The average reduction in OJ was 3.5 mm, and the OB correction averaged 2.1 mm. Cephalometric analysis showed positive changes in skeletal relationships, with a mean reduction in the angle formed by point A, nasion (N) and point B. (ANB) angle of 2.8 degrees. These improvements were statistically significant compared to the control group (P < 0.05). Conclusion: Early orthodontic intervention, such as interceptive orthodontics, has a positive impact on dental and skeletal development in children with mixed dentition.